What Will Be the Impact of the COVID-19 Quarantine on Psychological Distress? Considerations Based on a Systematic Review of Pandemic Outbreaks - Cavicchioli, Marco (Healthcare (Basel), 2021)
Background: The novel coronavirus (SARS-CoV-2) and related syndrome (COVID-19) has led to worldwide measures with severe consequences for millions of people. In the light of the psychopathological consequences of restrictive measures detected during previous outbreaks, a systematic review was carried out to provide an evidence-based assessment of possible effects of the current COVID-19 quarantine on mental health. Methods: This review included studies that assessed mental health indexes (e.g., overall psychological distress, depressive and PTSD symptoms) during and after quarantine periods adopted to management different outbreaks (e.g., COVID-19, SARS, MERS). Results: Twenty-one independent studies were included for a total of 82,312 subjects. At least 20% of people exposed to restrictive measures for the management of pandemic infections reported clinically significant levels of psychological distress, especially PTSD (21%) and depressive (22.69%) symptoms. Overall, original studies highlighted relevant methodological limitations. Conclusions: Nowadays, almost one out of every five people is at risk of development of clinically significant psychological distress. Further research on mental health after the current COVID-19 quarantine measures is warranted.